(4-Oxo-1,4-dihydropyridin-1-yl) acetic acid - Gao, S.; Ng, S.W.; Zain, Sharifuddin Md; Zhao, J.G.; Huo, L.H.; Zhang, Z.Y. (International Union of Crystallography, 2004)
The title compound, expected to be a betaine, 4-hydroxypyridinioacetate, HOC5H4N+CH2CO2- or C7H7NO3, on the basis of its synthesis by the nucleophilic displacement of chloride from the chloroacetate ion in water, exists as (4-oxo-1,4-dihydropyridin-1-yl)acetic acid. The acid H atom interacts with the oxo O atom of an adjacent molecule to form a linear helical chain [O⋯O = 2.451 (3) Å]. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.